A 22 GHz radio telescope - Mutch, Laurence Ian (Rhodes University, Faculty of Science, Department of Physics, 1976)
This thesis reports on the design, construction, testing and operation of the spectral line and continuum receivers built for the 22 GHz Radio Telescope. First results from 'the telescope were obtained and have been analysed to give an estimate of system efficiency. Tests have been performed on the front end and in particular on the 22 GHz mixer in order to determine the minimum detectable temperature. The Sun, Moon and major planets are sources suitable for antenna alignment and consequently a literature survey of emission at 22 GHz from elements of the Solar system has been made.
Keywords: Radio telescopes; Paraboloid; Radio astronomy